Influence Of Digital Leadership on Perceived Gender Equality, Collegiality, Wellbeing, And Organizational Commitment Among Academic Staff at Malaysian Tertiary Institutions - Yuk, Fong Chin; Sabariah Sharif; Fung, Lan Yong (Korean Society of Phycology, 2023)
The purpose of this study was to examine the influence of digital leadership on perceived gender equality, collegiality, wellbeing and organizational commitment among academic staff at Malaysian tertiary institutions. A review of the available literature indicates that there is a lack of empirical findings on digital leadership in relation to these four psychosocial constructs within the Malaysian context. The respondents of this study consisted of 100 academic staff based in five private tertiary institutions in Malaysia. The SPSS 26 was utilized to analyze the data which was collected online using close-ended questionnaires. Besides the item “gender equality”, there were no significant differences concerning the respondents’ perceptions of digital leadership. In addition, the Kruskal-Wallis H test showed no significant differences related to the age groups, academic credentials or work experiences of the respondents regarding how they perceived the correlations between digital leadership with collegiality, wellbeing and organizational commitment.